2012
DOI: 10.1093/europace/eus251
|View full text |Cite
|
Sign up to set email alerts
|

Value of P-wave signal averaging to predict atrial fibrillation recurrences after pulmonary vein isolation

Abstract: A FPD >140 ms is a marker of AF recurrences after RFCA and probably reflects the extent of atrial remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 33 publications
6
48
0
Order By: Relevance
“…Although this technique is still not widely used, it confirms that prolonged P-wave duration probably reflects inter- and/or intra-atrial conduction delays and could be related to the extent of atrial scarring and fibrosis, as shown by the longer P-wave duration in patients with recurrent AF 12 .…”
Section: Discussionmentioning
confidence: 72%
“…Although this technique is still not widely used, it confirms that prolonged P-wave duration probably reflects inter- and/or intra-atrial conduction delays and could be related to the extent of atrial scarring and fibrosis, as shown by the longer P-wave duration in patients with recurrent AF 12 .…”
Section: Discussionmentioning
confidence: 72%
“…To improve its signal-to-noise ratio, a signal-averaging approach is used. This technique has been widely considered for P-wave characterization, thus revealing clinically useful information, such as the identification of patients prone to PAF [41] or the prediction of AF recurrence after electrical cardioversion [42] or catheter ablation [43].…”
Section: Introductionmentioning
confidence: 99%
“…A cutoff value of ≥ 5 ms for the reduction in the P-wave had a sensitivity of 92 and a speci city of 71 to predict a good clinical outcome. For that reason, shortening of the FPD after PVI was reported to be a predictor of successful AF ablation 16,17 . In the present study, the results were the opposite of those reported in these previous studies.…”
Section: Discussionmentioning
confidence: 99%